Gabriel García Márquez and Ethics in One Hundred Years of Solitude - I - Herrera Molina, S.J,, Luis Carlos; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2015)
This reflection on Ethics in One Hundred Years of Solitude is divided in two main parts and issues. In this, the first one, thanks to the intertextual method, the author makes a journey throughout the structure, the characters and the focus of the novel to argue that ethics described there by Gabriel García Márquez is rooted in biblical myths, and how its use is a tool that gives unity to the work, and allows the author to openly reveal the human condition.